Empowerment of Mangrove-Based Community Groups in Improving Karawang's Household Economy - Yeni Sari Wulandari; Ali Fahmi Syahputra; Enjang Suherman; Ayuni Adzahra; Lalas Ade Lia; Winda Suci Oktavia; Wiyanda Wahyu Ristiyani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Mangrove pasir putih cilamaya kulon karawang is a 20-hectare beach and mangrove forest tourism area. As a conservation area, eco-tourism mangrove pasir putih cilamaya kulon itself is projected to be able to save the pasir putih fishing village area, which was previously threatened by erosion. Mangroves can also have economic value, but many people do not know that mangroves have many benefits and can increase income. The purpose of this community service activity is to empower the community through diversification of mangrove product processing in the form of mangrove batik, mangrove soap and dodol in improving community skills related to processing and marketing of good mangrove processed products. To increase the sales and household income of the community around the white sand mangrove tourism. The partner in the implementation of this service is prpm pasir putih, which oversees the management activities of tourism and mangrove forests in sukajaya village.